Analysis of the association between cetp taq1B polymorphism (rs708272) and cholesterol lowering effects among statin users with hyperlipidaemia from HUSM : a pilot study - Rahman, Ilani Ab (2018)
Statin, a cholesterol lowering agent, is widely used for treatment of hyperlipidemia (HPL) nowadays. Generally, statin is effective in reducing cholesterol level. However, there is a marked inter-patient variation with regard to response to statin treatment possibly due to differences in patients’ genetic makeup, their demographic profiles, and other clinical factors. A single nucleotide polymorphism(SNP) in Cholesteryl Ester Transfer Protein (CETP) Taq1B (rs708272) gene was reported as a promising predictive genetic marker for cholesterol lowering effect in many populations Until now, there is no genetic association study among Malaysian population has been explored the influence of the particular SNP on statin’s cholesterol lowering effects. Hence, we aim to study the association of CETP Taq1B (rs708272) variants together with other clinical factors on cholesterol lowering effect of statin among HPL patients from Hospital Universiti Sains Malaysia (HUSM), Kelantan. This is a retrospective study which involves 81 HPL patients. The details regarding demographic and clinical characteristics of patients were obtained via interview and patient’s medical record. The genotyping of DNA samples of HPL patients were performed by using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP). The results indicate that there were no significant association between patients’ demographic profiles as well as clinical factors and their statin cholesterol lowering effects. Interestingly, variant in CETP Taq1B rs708272 has been associated with statin’s cholesterol lowering effects for a certain degree. In homozygousmutant patient with B2B2 (AA) genotype has higher HDL-C level (P<0.05) than other genotypes (1.39±0.33 vs 1.29±0.32 and 1.26±0.29). The LDL-C and TC level were decreased significantly (P<0.01) in heterozygous variant patient with B1B2 (AG) genotype. While TG level was decreased significantly in B1 carrier. This finding warrants further multicenter investigation to confirm the association of the SNP with regards to the statin effectiveness on both LDL-C and HDL-C profile.